IMPLEMENTATION OF MUDHARABAH CONTRACTS IN SYARIAH BANK - Mutia Wulandari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
In the aspect of Islamic banking, mudharabah contracts are a type of contract that is quite common in various types of products and programs offered by Islamic banks. One of the Islamic bank products that has operational provisions using a mudharabah contract is financing or the process of borrowing capital.One of the highlights is financing using a mudharabah contract. Mudharabah itself can be interpreted as a cooperation contract between two parties in which the first party provides all the funds, while the second party acts as the manager of the funds and profits are shared between them according to the agreement while losses are only borne by the owner of the funds.